CHALLENGES RELIGIOUS TELEVISION, BETWEEN BUSINESS AND DA’WAH: STUDY OF TV9 NAHDLATUL ULAMA INDONESIA - Handoko, Daniel; Sakti, Andi Muhammad Tri; Said, Bambang Suhartono bin Mohd (Universitas Muhammadiyah Jakarta, 2024)
Television has the advantage that it is audio-visual (seen and heard), it can depict reality and also present events that are happening. TV9 Nahdlatul Ulama is a television station based on religious values. This TV was founded by the largest religious organization in Indonesia. As an economic institution, television is not only used as a means to spread organizational ideologies, but also takes into account business aspects to do well. This study aims to examine the performance of a religious television station amidst the intense competition in the television industry in Indonesia, and how media performance is affected by financial sources. By conducting in-depth interviews with key informants and direct observation, this research found that TV9 practices management principles in media management, even though there are several considerations for Nahdlatul Ulama management, TV9 involves personnel from Nahdlatul Ulama members in aspects of its management so that ideological transformation can run well. From the aspect of broadcast media performance, TV9 benefits from the very large mass base of Nahdlatul Ulama members in Indonesia. TV9 focuses on including Kiayi and Bunyai as inspiration for television program design and also includes Islamic boarding schools. In the culture of NU, Kiayi and Bunyai have a strategic position in the religious tradition of Nahdlatul Ulama.